1971
DOI: 10.1073/pnas.68.6.1351
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Complement Pathway: C-3 Cleaving Activity, Not Due to [unk], on Endotoxic Lipopolysaccharide after Treatment with Guinea Pig Serum; Relation to Properdin

Abstract: The reaction between endotoxic lipopolysaccharide (LPS) and the guinea pig complement system was shown to proceed by way of an intermediate complex, LPS-X, which contains at least six guinea pig serum proteins. LPS-X, like EAC4,2a (sheep erythrocytes carrying antibody molecules and C4,2a complexes), destroys the C3 molecule by cleavage. On incubation at 370C, LPS-X loses its capacity to destroy C3 at about the same rate as the decay of EAC4,2a, so that it has been assumed that LPS-X carries C4,2a sites that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1972
1972
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…2). The IC so was 4.6 x 10-8 M. This result showed that its activity was much higher than those of lipopolysaccharide (Gewurz et al, 1968: Marcus et al, 1971, 6-branched,~(l~3)glucan (Hamuro et al, 1978), arabinan -…”
Section: Anticomplementary Activitymentioning
confidence: 71%
See 1 more Smart Citation
“…2). The IC so was 4.6 x 10-8 M. This result showed that its activity was much higher than those of lipopolysaccharide (Gewurz et al, 1968: Marcus et al, 1971, 6-branched,~(l~3)glucan (Hamuro et al, 1978), arabinan -…”
Section: Anticomplementary Activitymentioning
confidence: 71%
“…The activation of complement releases C3 a , C4 a , and C5 a , but they result in organ transplant rejection (Miyagawa et al, 1988;Dimond, 1995), asthma, allergy, atopys dermatitis (Groggel et al, 1983;Rother et al, 1985;Strunk et al, 1988;Alexandef et al, 1988;McGeer and McGeer, 1995), arthritis, systemic lupus erythematosus and ARDS (Carson, 1985;Murry et al, 1988;Zvaifler, 1989). For the prevention and treatment of these diseases, anticomplementary polysaccharides, for example, lipopolysaccharide (Gewurz et al, 1968;Marcus et al, 1971), 6-* Author to whom correspondence should be addressed. Muller-Eberhard, 1971) have already been isolated from bacteria, fungi and plants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been emphasized that the complement system can be activated by alternate pathways (21)(22)(23)(24). Sera deficient in Clr provided a useful new reagent with which to study the concept of the alternate pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Electron micrographs of gram-negative bacteria after incubation with antibody and complement demonstrate the development of circumscribed defects in the bacterial cell walls (1,2). The in vitro incubation of endotoxin with a variety of animal sera results in the inactivation of selected complement components with the generation of complement-derived chemotactic and anaphylatoxic factors (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) Received for publication 9 June 1972 and in revised form 10 October 1972.…”
Section: Introductionmentioning
confidence: 99%